Central Bank Independence and Transparency : Evolution and Effectiveness - Crowe, Christopher (IMF Working Papers; Working Paper ;, 2008)
This paper examines the current level of central bank independence (CBI) and transparency in a broad sample of countries using newly constructed measures, and looks at the evolution in both measures from an earlier time period. Increases in CBI have tended to occur in more democratic countries and in countries with high levels of past inflation. More independent central banks in turn tend to be more transparent, while transparency is also positively correlated with measures of national institutional quality. Exploiting the time dimension of our data to eliminate country fixed effects and using instrumental variable estimation to overcome endogeneity concerns, we present evidence that greater CBI is associated with lower inflation. We also find that enhanced transparency practices are associated with the private sector making greater use of information provided by the central bank.